Scoby-Doo Unmasking the Gut Microbiota Through Hands-On Kombucha Making for Adolescents - Siti Azyyati Nur Shadrina; Alexandra, Gabriella; Panggabean, Adinda Cleo Putri; Abdillah, Naia Dalila; Reizaputra, Hafizh Al-Ghazali; Putra, Rajendra Apta Riansa; Anggaputra, Raden Muhammad Risyad Febrirachmadi; Tamu, Putu Wecan Indah Wahyu; Narindra, Roro Ayu Terrani Kusuma; Aminudin, Kemal Isra; Istav, Naadhira Lillianne Fania; Indriasari, Vita (Lembaga Teewan Journal Solutions, 2026)
Gastrointestinal health is largely determined by the balance of the gut microbiota, a community of microorganisms that play a vital role in maintaining epithelial barrier function, modulating immune responses, and synthesizing essential metabolites such as short-chain fatty acids and vitamins. Disruption of this balance can trigger dysbiosis, which is associated with various digestive, inflammatory, and metabolic disorders. Therefore, maintaining a healthy microbiota through the intake of natural probiotics is an important preventive step that should be promoted early among adolescents. Interactive counseling was combined with a kombucha-making demonstration and tasting, using a fun-learning approach themed “SCOBY-DOO” to engage participants. Twenty-seven ninth-grade students of SMP Al Ma’soem Jatinangor participated fully. Knowledge was assessed using parallel pre-test and post-test instruments on microbiota and probiotics, analyzed with a paired-samples t-test and Cohen’s d effect size. Analysis using the paired-samples t-test showed a significant increase in mean knowledge score from 80.96 on the pre-test to 92.85 on the post-test (p < 0.001). The Cohen’s d effect size was 1.03, falling in the large category, indicating a substantial impact of the intervention. Attendance reached 90%, and all participants enthusiastically completed every activity stage, including hands-on practice and discussion. Conclusion: The fun-learning educational approach combined with hands-on fermentation practice proved highly effective in improving adolescents’ digestive health literacy. Similar activities are recommended to be continued with longer discussion sessions and additional interactive media, such as digital quizzes or animated videos, to deepen participants’ understanding and reach more students